Scanning electron microscopic analysis of the sealing ability of GuttaFlow and Acroseal endodontic sealers - Teodorović Nevenka; Matović Ivan (Serbian Medical Society - Dental Section, Belgrade, 2008)
Introduction: The sealing ability of endodontic sealers to dentinal surfaces of root canals is an important feature of these materials. Root canal sealers are necessary to seal the spaces between the dentinal walls and the obturating core material. Aim: The aim of this study was to examine the sealing ability of two endodontic sealers to dentin walls and guttapercha cones using scanning electron microscopic analysis-SEM. Materials and Methods: 24 recently extracted human single-rooted teeth were instrumented and allocated to two groups; root canals were filled with either GuttaFlow (Roeko,Germany), a new endo-sealer (group 1), or Acroseal (Septodont, France), a calcium hydroxide based sealer, (group 2). The sealing ability and adhesion properties of the sealer-dentin interface were studied using SEM. Results: The specimens filled with GuttaFlow showed smooth contact lines at the sealer-dentin interface, and this material also showed strong bonding and good adaptation to guttapercha cones. Acroseal showed good adhesion to dentin walls, and bonding surface was represented as a slightly curved contact line, with some gaps on material-dentin walls and guttapercha cones interface. Conclusion: New GuttaFlow material possesses strong sealing ability and excellent adhesion to dentin walls and guttapercha cones. Acroseal showed good bonding to dentin and slightly weaker adhesion to guttapercha cones, in comparison to GuttaFlow.